2022
DOI: 10.1021/acs.macromol.2c01090
|View full text |Cite
|
Sign up to set email alerts
|

Precise Isotactic or Atactic Pendant Alcohols on a Polyethylene Backbone at Every Fifth Carbon: Synthesis, Crystallization, and Thermal Properties

Abstract: A semi-crystalline precision polymer with a high molar mass (>100 kg mol–1), a moderate dispersity (∼1.6), and an isotactic alcohol pendant on each and every fifth carbon of a linear polyethylene backbone is synthesized through highly regioregular ring-opening metathesis polymerization of (S) or (R)-3-(tert-butyldimethylsiloxy)­cyclopentene followed by olefin hydrogenation and alcohol deprotection. The thermal and semi-crystalline properties of these materials are compared to analogues with atactic alcohol pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…The indexing is essentially the same as that for it-PPMA. However, the a - and b -axial lengths are longer than those of it-PPMA case, thus indicating a more expanded lattice for at-PPMA in agreement with earlier predictions from WAXD patterns of non-oriented specimens . The ratio a / b = 1.73 suggests a pseudo-hexagonal packing of the molecular chains.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…The indexing is essentially the same as that for it-PPMA. However, the a - and b -axial lengths are longer than those of it-PPMA case, thus indicating a more expanded lattice for at-PPMA in agreement with earlier predictions from WAXD patterns of non-oriented specimens . The ratio a / b = 1.73 suggests a pseudo-hexagonal packing of the molecular chains.…”
Section: Resultssupporting
confidence: 87%
“…While the T g of both at-PPMA and it-PPMA is similar, ∼50 °C, the melting temperature ( T m ) and X c changed significantly. For at-PPMA and it-PPMA, T m = 125 and 190 °C, respectively, while the X c increased from 0.2 to 0.4 . One interesting feature from the comparative work was the effect of tacticity on segmental packing.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Tuba et al 28 studied ROMP of 3-hydroxycyclopentene without protecting groups; however, the resulting polymer had a low molar mass, and hydrogenation was not attempted on the ROMP-derived material. Very recently, Guillory et al 29 reported stereo-and regioregular EVOH made by ROMP of 3tert-butyldimethylsiloxycyclopentene and its enantiomerically pure derivatives. These polymers all displayed varying thermal properties due to their differing ethylene and vinyl alcohol concentrations, regio-and stereochemistry, and degrees of hydrogenation.…”
Section: ■ Introductionmentioning
confidence: 99%